2017
DOI: 10.1111/cod.12931
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene glycol as marker for nitrofurazone allergy: 20 years of experience from Turkey

Abstract: PEG sensitivity seems to be a marker for contact allergy to topical nitrofurazone in Turkey. Nitrofurazone allergy appears to favour concomitant sensitization to PEG. We would suggest the inclusion of PEG in an extended baseline patch test series in Turkey. Late patch test readings are important to diagnose delayed positive reactions to PEG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 31 publications
0
10
0
3
Order By: Relevance
“…Positive reactions may not always be achieved despite the use of allergens at appropriate concentrations in patch testing, which is extremely important in the assessment of ACD [14]. Ozkaya and Kılıç reported that late positive reactions to nitrofurazone, in which the reactions started on D4 or later (D7) in more than one-third of patients [9]. Because our study did not have late reading (D7), patch test results may be negative.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Positive reactions may not always be achieved despite the use of allergens at appropriate concentrations in patch testing, which is extremely important in the assessment of ACD [14]. Ozkaya and Kılıç reported that late positive reactions to nitrofurazone, in which the reactions started on D4 or later (D7) in more than one-third of patients [9]. Because our study did not have late reading (D7), patch test results may be negative.…”
Section: Discussionmentioning
confidence: 93%
“…Nitrofurazone sensitization has been known for many years. Studies reported in the literature generally show nitrofurazone susceptibility rates in patch test results with topical drugs in ACD suspected cases [8, 9]. There are not many studies reporting only nitrofurazone-related ACDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Controls were done in healthy volunteers resulting negative in all of them. Taking into account that there are studies that have reported delayed hypersensitivity reactions to PEGs [7], a patch test was performed with Betadine ® solution, GripaNait ® , Ziverel ® , polysorbate 80, and PEG 4000 10%, but it was negative in all products.…”
Section: Case Presentationmentioning
confidence: 99%
“…Various derivatives similar to lanolin alcohols exist, some of which were identified as contact allergens, such as cetearyl isononanoate [216]. Low-molecular weight polyethylene glycol is widely used in Turkey and has been found to be linked with nitrofurazone sensitisation, but has also been relevant when used in minoxidil solutions, and antiherpetic and corticosteroid creams [217]. Alkyl glucosides are widely used in cosmetics and other products, including a foam wound dressing, which caused ACD in a 70-year-old Belgian female [218], and several wound care and operative products causing ACD in 2 US patients [219].…”
Section: Medicines (Active Principles and Excipients) And Cosmeticsmentioning
confidence: 99%